1998
DOI: 10.1021/jo981619a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-[18F]Fluoroestradiol, a Potential Diagnostic Imaging Agent for Breast Cancer:  Strategies to Achieve Nucleophilic Substitution of an Electron-Rich Aromatic Ring with [18F]F-

Abstract: To improve the pharmacokinetics of fluorine-18 labeled estrogens to be used as receptor-based imaging agents for the identification and staging of estrogen-receptor-positive breast carcinoma, we wanted to synthesize 2-[(18)F]fluoroestradiol. This compound has high affinity for the estrogen receptor and also binds very well to sex hormone binding globulin, a protein thought to protect estrogens from metabolism and deliver them to target tissues. We anticipated that this compound might have increased tumor uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Many methods have been developed for the incorporation of fluorine-18 into a deactivated electron-rich aromatic ring by a nucleophilic aromatic substitution reaction. 1316 Recently, the use of diaryliodonium salts has received considerable attention as a one-step method of introducing fluorine-18 into ring structures with high radiochemical yields in electron-rich aromatic systems. 1721 This approach provides specific activities that are sufficiently high for successful PET imaging studies of receptors in various organs.…”
Section: Resultsmentioning
confidence: 99%
“…Many methods have been developed for the incorporation of fluorine-18 into a deactivated electron-rich aromatic ring by a nucleophilic aromatic substitution reaction. 1316 Recently, the use of diaryliodonium salts has received considerable attention as a one-step method of introducing fluorine-18 into ring structures with high radiochemical yields in electron-rich aromatic systems. 1721 This approach provides specific activities that are sufficiently high for successful PET imaging studies of receptors in various organs.…”
Section: Resultsmentioning
confidence: 99%
“…H-bonding has been attributed to play a predominant factor in the transport of estrogens in biological systems [37][38][39][40][41][42]. The hormones such as E1, E2 and DES all possess a phenol group which is electron rich [43] and can therefore have the potential to form π-π bonding with electron deficient phenyl groups [30] of the polymers.…”
Section: Micropollutant Characteristics: the Group Of Estrogensmentioning
confidence: 99%
“…If electron-withdrawing groups less potent than cyano are present on the trimethylanilinium ring, radiofluorination yields begin to decline. Corrected radiofluorination yields for para-trimethylammonium aryl aldehydes [24][25][26][27], ketones [28][29][30][31][32], and esters [33][34][35][36] range from excellent (80%) for aryl aldehydes to fair (50%) for aryl esters. For relatively unactivated rings, fluorodeamination is difficult; Ermert and coworkers [37] studied substitution in 4-bromo-N,N,N-trimethylanilinium triflates and found that only 8-12% yields of the desired 4-fluorobromobenzenes were obtained under optimized conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of [ 18 F] methyl fluoride has been observed in some cases where it is suspected to be the main deleterious side reaction [11,28]. The reverse Menschutkin reaction was also exploited for the preparation of labeled methyl fluoride; 2-acetyl-N,N,N-trimethylanilinium triflate readily undergoes microwave-induced [ 18 F] fluorodemethylation [39].…”
Section: Introductionmentioning
confidence: 99%